Oral health-related quality of life and severity of periodontal disease - Neetha Bhargava; Atul Jadhav; Pratiksha Kumar; Aliza Kapoor; Durga Prasad Mudrakola; Sandeep Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Oral diseases are among the most common diseases which could not dissociate from general conditions with regards to impacts on quality of life (QoL). The present study is aimed to assess the impact of the severity of periodontal disease on oral health QoL using oral health-related quality of life (OHQoL)-UK questionnaire. Materials and Methods: The OHQoL-UK questionnaire consists of 16 variables within four domains made up of symptoms, psychological, social dimensions, and physical dimensions. Summing up the responses produce overall OHQoL-UK scores ranging from 16 to 80. Internal consistency was assessed using Cronbach's reliability coefficient. Each patient underwent a periodontal examination including periodontal attachment levels with Williams' periodontal probe as part of his or her routine assessment by one clinician collaborating on the study. Results: Within 200 patients participating in this study, 51% were < diploma, 32% were < bachelor's degree, and 17% were bachelor's degree and higher. Patients with higher educational level have a higher mean QoL score (P = 0.0001) which was statistically significant in regard to all aspects. Conclusion: The mean QoL score was significantly lower in patients with severe periodontitis when compared to patients with mild periodontitis, patients with better academic qualification have higher mean QoL score. According to the effect of severity of periodontal condition and educational level on QoL, required intervention should be done for treatment to improve QoL as a result.